Tracing the Image of Turks in Travel Writing through Translation - Seda Taş İlmek (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
The main aim of this study is to examine how the images of Turks were depicted in the travel writing A Journey through the Crimea to Constantinople, written by the English traveler Elizabeth Craven, and to trace their repatriation into Turkish through translation entitled 1786’da Türkiye (Turkey in 1786) by the translator Reşat Ekrem Koçu. This study benefits from an imagological perspective in its methodology and applies a comparative textual analysis, which puts a particular emphasis on the abundance of negative images of Turks in the source text and reflects the scarcity of such images in the target text. The analysis, from an imagological lens, shows that the heteroimages of Turks, which were mostly constructed through negative implications by the foreign writer, were lost in their repatriation to their own culture. In other words, the negative images of Turks were largely omitted from the target text, and the source text was abridged to a large extent by the Turkish translator, revealing the fact that the Other’s negative views about the Turks could not cross the borders at all. This, naturally, leads the text with a pejorative tone towards the Turks to be rewritten as a target text having a commendatory tone due to the presence of a plethora of positive Turkish imagery along with the paratextual additions such as several illustrations, comments, the translator’s preface, and the publisher’s note. Therefore, the analysis suggests that the translator, as an intercultural agent, seemed to claim his position as an author-translator in the translation process while particularly illustrating the function of gatekeeping and the use of translation for selecting and highlighting the representation of mental pictures of a certain culture and period.